2019
DOI: 10.1021/jacs.8b10002
|View full text |Cite
|
Sign up to set email alerts
|

H/D Isotope Effects Reveal Factors Controlling Catalytic Activity in Co-Based Oxides for Water Oxidation

Abstract: Understanding the mechanism for electrochemical water oxidation is important for the development of more efficient catalysts for artificial photosynthesis. A basic step is the proton-coupled electron transfer, which enables accumulation of oxidizing equivalents without buildup of a charge. We find that substituting deuterium for hydrogen resulted in an 87% decrease in the catalytic activity for water oxidation on Co-based amorphous-oxide catalysts at neutral pH, while 16O-to-18O substitution lead to a 10% decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 78 publications
12
92
1
Order By: Relevance
“…A common starting point is the involvement of equivalent reactive moieties in both molecular and heterogeneous WOCs at the atomic level. 14 Specifically, the surface of a finite particle offers localized molecular centers for catalytic reactions, while some key molecular motifs are essentially surface cut-outs of solids. These structural similarities clearly link both fields for a mutual transfer of insight, which is beneficial and indispensable for optimizing the performance and durability of WOCs in general.…”
Section: S Esmael Balaghi Received His Bsc In Chemistry From Shiraz mentioning
confidence: 99%
See 1 more Smart Citation
“…A common starting point is the involvement of equivalent reactive moieties in both molecular and heterogeneous WOCs at the atomic level. 14 Specifically, the surface of a finite particle offers localized molecular centers for catalytic reactions, while some key molecular motifs are essentially surface cut-outs of solids. These structural similarities clearly link both fields for a mutual transfer of insight, which is beneficial and indispensable for optimizing the performance and durability of WOCs in general.…”
Section: S Esmael Balaghi Received His Bsc In Chemistry From Shiraz mentioning
confidence: 99%
“…Furthermore, a reduction of the activity by 10% was observed when 18 O isotope tests were performed, which served as evidence for the direct coupling of Co IV -oxo species during the RDS. 14 2.1.2. Hematite.…”
Section: Mechanistic Advances For Heterogeneous Wocsmentioning
confidence: 99%
“…This is explained by an increase in the electrolyte pH in the presence of larger cations due to the higher basicity of the corresponding alkali hydroxide. In recent findings by Pasquini et al 63 the catalytic rate of a CoO x catalyst was found to be controlled by the levels of oxidized Co 4+ at any defined OER overpotential. A similar scenario could prevail in our Ni-Fe catalyst, although, we do not find as strong correlation with the population of oxidized Ni (3+δ)+ during steady-state conditions and the OER activity.…”
Section: Discussionmentioning
confidence: 94%
“…• In-situ characterization of materials under catalysis conditions with low-temperature data collection (freeze-quench approach, Klingan et al, 2018;Pasquini et al, 2019, Bergmann et al, 2020Smith et al, 2017) • Operando XAS on films for water oxidation reaction (OER) under electrochemistry conditions at room temperature (Smith et al, 2017;González-Flores et al, 2018) • XAS on dilute-solution (1 mM) protein samples at cryogenic conditions (Reschke et al, 2019) • Rapid-scan EXAFS (redox transitions and catalytic processes during cyclic voltammetry) • EXAFS as a function of chemical composition and/or temperature dependent EXAFS (Kesavan et al, 2020) 3 Technical data (a) XAS experiments at cryogenic (cryostat) or operando (electrochemistry) conditions can be performed in parallel using two energy-resolving detectors. (b) Rapid data readout/transfer (e.g.…”
Section: Instrument Applicationmentioning
confidence: 99%